1973
DOI: 10.1002/kin.550050109
|View full text |Cite
|
Sign up to set email alerts
|

The homogeneous gas phase H2D2 metathesis at room temperature: Reaction induced by specific vibrational excitation

Abstract: We have demonstrated that reactions for which substantial activation energies are needed can be induced to occur at room temperature via specific vibrational excitation.Indeed, the indications are that the atom-switching reactions for which E, > 25 kcal take place with high probability only when the activation energy is localized in the vibrational mode. In this preliminary report on the utilization of the stimulated Raman effect to generate substantial populations in the critical vibrational states required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1973
1973
1987
1987

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…However, in the studies at hand, the product HOD+ is observed at collision energies below 1 eV, with H2+ reagents which have up to 2.6 eV of internal excitation. The role of reagent internal excitation in promoting the four-center H2 + D2 reaction has been emphasized in the laser excitation experiments of Bauer et al,31 the interpretation of which is consistent with the present work in which H2+ vibrational excitation may be efficacious in surmounting a symmetry-imposed barrier.…”
Section: Discussionsupporting
confidence: 91%
“…However, in the studies at hand, the product HOD+ is observed at collision energies below 1 eV, with H2+ reagents which have up to 2.6 eV of internal excitation. The role of reagent internal excitation in promoting the four-center H2 + D2 reaction has been emphasized in the laser excitation experiments of Bauer et al,31 the interpretation of which is consistent with the present work in which H2+ vibrational excitation may be efficacious in surmounting a symmetry-imposed barrier.…”
Section: Discussionsupporting
confidence: 91%
“…For the simpler H2 + D2 reaction, these equations have been solved with the result that the value of z changes from 1.2 to 3 without an induction period. 22 It has been suggested that the reaction of C2N2 with D2 to form DCN would be faster than C2N2 with H2 if VEX were the dominant mechanism.23 This prediction is related to the observation reported in the single-pulse shock tube study of the H2 + D2 exchange that the rate depended more strongly on the concentration of D2 than on H2.21. 24 In the temperature range 1050-1200°K, the rate of D2 with C2N2 was found to be faster than that of H2 with C2N2 although the rate decreased with increasing temperature.23…”
Section: Discussionmentioning
confidence: 98%
“…The importance of the vibrational energy content of the reactants has been emphasized and the observed nonlinear time dependence for product formation supports the contention that there exists a nonequilibrium step(s) in the exchange mechanism. 21 The determination of non-zero-order dependencies for the inert gas diluent argues also for a multistep process involving excitation of the reactants prior to exchange.…”
Section: Discussionmentioning
confidence: 99%